AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-1346
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Approaches to Multi-Body Relative Motion using the Kestrel Solver

Abstract: Time-step (s) ̅ Wing mean aerodynamic chord (m) , , Axial, normal and side force coefficient , , Rolling, pitching & yawing moment coefficient Subset distance (in) Store diameter, model scale (1in) Inflation layer total height (0.138in) CPU time per iteration (s)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Unlike the steady-state simulation, for the trajectory prediction, it can be observed that solving the viscous flow even with very well prepared meshes may not necessarily provide better results than the Euler solution. A similar observation can be made by reviewing the results of Figure 19 in Huang et al 30
Figure 30.Roll angle of the store. Comparison between the Euler and Navier–Stokes solutions for the fine mesh.
Figure 31.Pitch angle of the store.
…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Unlike the steady-state simulation, for the trajectory prediction, it can be observed that solving the viscous flow even with very well prepared meshes may not necessarily provide better results than the Euler solution. A similar observation can be made by reviewing the results of Figure 19 in Huang et al 30
Figure 30.Roll angle of the store. Comparison between the Euler and Navier–Stokes solutions for the fine mesh.
Figure 31.Pitch angle of the store.
…”
Section: Resultssupporting
confidence: 67%
“…For the transient run, the angular displacements results are shown in Figures 30–32 for roll, pitch, and yaw angles, respectively. The work of Huang et al 30 can be considered as a comprehensive study which analyzed the effect of the mesh (size and topology), the model scale, the wing symmetry, and the turbulence models. Their best Navier–Stokes result for angular displacements (using Spalart–Allmaras turbulence model 31 ) has been included along the work of Sunay et al 6 in these figures and compared with the present results for both Euler and Navier–Stokes simulations.…”
Section: Resultsmentioning
confidence: 99%